Hak Regres Penanggung pada Jaminan Perorangan Dalam Kepailitan - Madeleine Celandine (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe credit agreement as the principal agreement between the debtor and the creditor can acquire additional collateral providing material collateral and individual collateral. Personal collateral for individual rights, which is the agreement of a third party to bind themselves to debtors and creditors involved in credit agreements in accordance with the interests of creditors. In the event that the debtor does not have assets and is unable to repay debts to the creditor, the person responsible for paying the creditors' reserves and is obliged to pay debts to the creditor. The responsibility of the person responsible for compiling the debtor is not carried out by the creditor and the person responsible for the release of their privileges. The guarantor who has agreed to pay the debtor according to the law obtained by the right of regres, namely the right to recover from the payment owned. An interesting discussion about this Guarantee relates to the bankruptcy law regarding the enforcement of the right to regress so that it can be held accountable for receiving payments made. Keywords: Regress Rights; Personal Guarantee; Bankruptcy.AbstrakPerjanjian kredit sebagai perjanjian pokok antara debitor dengan kreditor dapat melahirkan jaminan tambahan berupa jaminan kebendaan dan jaminan perorangan. Jaminan perorangan melahirkan hak perorangan, yang merupakan persetujuan pihak ketiga untuk mengikatkan diri kepada debitor dan kreditor yang terlibat dalam perjanjian kredit demi kepentingan kreditor. Dalam hal debitor tidak memiliki harta kekayaan dan tidak mampu membayar utang kepada kreditor, maka penanggung berperan sebagai cadangan debitor dan wajib membayarkan utang kepada kreditor. Tanggung jawab penanggung lahir ketika debitor tidak melaksanakan kewajiban kepada kreditor dan penanggung telah melepaskan hak istimewa yang dimiliki. Penanggung yang telah menggantikan pembayaran debitor demi hukum memperoleh hak regres, yaitu hak untuk menuntut kembali atas pembayaran yang dimiliki. Pembahasan yang menarik mengenai jaminan ini berkaitan dengan hukum kepailitan mengenai penegakan hak regres agar dapat diakui sebagai utang untuk dapat memperoleh piutang pembayaran yang telah dilakukan. Kata Kunci: Hak Regres; Jaminan Perorangan; Kepailitan.